2021
DOI: 10.21307/ane-2021-010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental chronic sleep fragmentation alters seizure susceptibility and brain levels of interleukins 1β and 6

Abstract: Brain hyperexcitability in sleep apnea is believed to be provoked by hypoxemia, but sleep fragmentation can also play a significant role. Sleep fragmentation can trigger inflammatory mechanisms. The aim of this research was to investigate the effects of chronic sleep fragmentation on seizure susceptibility and brain cytokine profile. Chronic sleep fragmentation in male rats with implanted EEG electrodes was achieved by the treadmill method. Rats were randomized to: treadmill control (TC); activity control (AC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…The deficiency of synapsin-IIa and IIb isoforms is crucially associated with epileptiform and seizure-related phenomena due to its regulation of neurotransmitter release. 17 Grubač et al 18 reported that chronic sleep fragmentation increases seizure susceptibility and modulates neuronal production of IL-1β and IL-6. According to Grippo et al, 19 the PaCO2 level in patients with obstructive sleep apnea may interact on various ion channels or metabolic pathways, changing the excitability of the motor cortex and modifying excitatory and inhibitory cortical circuits.…”
Section: Discussionmentioning
confidence: 99%
“…The deficiency of synapsin-IIa and IIb isoforms is crucially associated with epileptiform and seizure-related phenomena due to its regulation of neurotransmitter release. 17 Grubač et al 18 reported that chronic sleep fragmentation increases seizure susceptibility and modulates neuronal production of IL-1β and IL-6. According to Grippo et al, 19 the PaCO2 level in patients with obstructive sleep apnea may interact on various ion channels or metabolic pathways, changing the excitability of the motor cortex and modifying excitatory and inhibitory cortical circuits.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is an important neuroinflammatory factor that mediates brain inflammatory lesions and amyloidosis, and is associated with a variety of brain diseases, including Alzheimer's disease, and autism (10,11). IL-6 is associated with periventricular leukomalacia and may affect neurodevelopment and increase the risk of cerebral palsy (12). Studies have shown that in children with cerebral palsy, cytokines are dysregulated, and plasma TNF levels are elevated (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, under physiological conditions, Il1b seems to modulate several functions in the CNS, such as regulating sleep (De Sarro et al 1997 ; Krueger et al 1998 ) and promoting learning and long-term potentiation (LTP) (Bellinger et al 1993 ; Schneider et al 1998 ; Ikegaya et al 2003 ; del Rey et al 2013 ). Chronic overexpression of Il1b in brain areas such as the hippocampus have been implicated in impaired spatial memory (Moore et al 2009 ) and in contextual fear memory (Matousek et al 2010 ) in conditional transgenic mice, and with seizure susceptibility in animal models of sleep fragmentation (Grubac et al 2021 ) and prostatitis (Sutulovic et al 2019 ). By contrast, transgenic mice with deficient Il1b signaling or pharmacological inhibition of CNS Il1b also present with memory and learning impairment (Avital et al 2003 ; Goshen et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%